Wastewater and environmental sampling holds potential for antimicrobial resistance surveillance in food-producing animals - a pilot study in South African abattoirs - Heljanko, Viivi; Karama, Musafiri; Kymäläinen, Amanda; Kurittu, Paula; Johansson, Venla; Tiwari, Ananda; Nyirenda, Matteo; Malahlela, Mogaugedi; Heikinheimo, Annamari (Frontiers in Veterinary Science, 2024)
Antimicrobial resistance (AMR) poses a significant global One Health challenge that causes increased mortality and a high financial burden. Animal production contributes to AMR, as more than half of antimicrobials are used in food-producing animals globally. There is a growing body of literature on AMR in food-producing animals in African countries, but the surveillance practices across countries vary considerably. This pilot study aims to explore the potential of wastewater and environmental surveillance (WES) of AMR and its extension to the veterinary field. Floor drainage swab (n = 18, 3/abattoir) and wastewater (n = 16, 2-3/abattoir) samples were collected from six South African abattoirs that handle various animal species, including cattle, sheep, pig, and poultry. The samples were tested for Extended-Spectrum Beta-Lactamase (ESBL) and Carbapenemase-producing Enterobacterales, Methicillin-Resistant Staphylococcus aureus (MRSA), Vancomycin-resistant Enterococci (VRE), and Candida auris by using selective culturing and MALDI-TOF MS identification. The phenotype of all presumptive ESBL-producing Escherichia coli (n = 60) and Klebsiella pneumoniae (n = 24) isolates was confirmed with a disk diffusion test, and a subset (15 and 6 isolates, respectively), were further characterized by whole-genome sequencing. In total, 314 isolates (0–12 isolates/sample) withstood MALDI-TOF MS, from which 37 species were identified, E. coli and K. pneumoniae among the most abundant. Most E. coli (n = 48/60; 80%) and all K. pneumoniae isolates were recovered from the floor drainage samples, while 21 presumptive carbapenem-resistant Acinetobacter spp. isolates were isolated equally from floor drainage and wastewater samples. MRSA, VRE, or C. auris were not found. All characterized E. coli and K. pneumoniae isolates represented ESBL-phenotype. Genomic analyses revealed multiple sequence types (ST) of E. coli (n = 10) and K. pneumoniae (n = 5), including STs associated with food-producing animals globally, such as E. coli ST48 and ST10 and K. pneumoniae ST101. Common beta-lactamases linked to food-producing animals, such as blaCTX-M-55 and blaCTX-M-15, were detected. The presence of food-production-animal-associated ESBL-gene-carrying E. coli and K. pneumoniae in an abattoir environment and wastewater indicates the potential of WES in the surveillance of AMR in food-producing animals. Furthermore, the results of this pilot study encourage studying the topic further with refined methodologies.